Homelessness in America and U.S. Foreign Policy toward Africa: Westward Migration and Implications for Nigeria - Abang, Mkpe (Journal of Contemporary International Relations and Diplomacy, 2026)
This article examines the problem of homelessness in the United States, as well as American foreign policy and implications for Nigerian migration. While the U. S. projects a model of prosperity, democracy, and opportunity, America’s domestic reality is marred by widespread homelessness, structural inequality, and racialised marginalisation. Using qualitative methodology, the study examines how these contradictions undermine U.S. soft power credibility abroad and exposes the fragility of the “American Dream.” The discussion situates Nigerian migration within a broader historical continuum linking transatlantic slave trade to contemporary visa regimes, showing how structural dependency and racialised exclusion persist under new forms. The article argues that Nigerian migrants are often lured by aspirational narratives of opportunity but face harsh realities of job precarity, disillusionment, and homelessness in America. These lived experiences resonate with a wider collapse of U.S. moral authority in Africa, as the same state that criminalises African poverty struggles to address its own systemic crises. The article argues for a recalibration of Nigeria’s foreign policy, media narratives, and migration diplomacy through an Afrocentric framework that promotes African authority, regional integration, and self-reliance. By deconstructing the mirage of American exceptionalism, the study calls for Nigeria and other African states to pursue development strategies rooted in Afrocentric engagement rather than dependency on flawed Western models.